2017
DOI: 10.1007/s00520-017-3880-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term quality of life profile in oncology: a comparison between cancer survivors and the general population

Abstract: Purpose Understanding the quality of life (QoL) of cancer survivors is relevant to both clinical practice and health care policy. The current study compared the QoL profile in this specific population with that of a normative sample for the general population, as well as with those of both healthy and oncological patients normative sub-samples. In addition, associations between the obtained QoL profile and the main socio-demographic and clinical characteristics of the sample were examined. Methods Three hundre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 20 publications
5
32
0
Order By: Relevance
“…The lack of communication between survivor and co‐worker can be a barrier to successful working life after diagnosis, limiting the meaning of work and its role in recovery. Furthermore, previous research has found differences between the QoL of cancer survivors and their peers even in the long term, which were confirmed in our results. Also here, employed cancer survivors, who had been diagnosed at least 2 years earlier, presented a lower overall QoL than the general population.…”
Section: Discussionsupporting
confidence: 92%
“…The lack of communication between survivor and co‐worker can be a barrier to successful working life after diagnosis, limiting the meaning of work and its role in recovery. Furthermore, previous research has found differences between the QoL of cancer survivors and their peers even in the long term, which were confirmed in our results. Also here, employed cancer survivors, who had been diagnosed at least 2 years earlier, presented a lower overall QoL than the general population.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, that sample had higher levels of education when compared with our study sample. It has been previously shown that cancer survivors with higher education tend to report better HRQOL [19,20]. The Canadian sample was older than our sample.…”
Section: Discussionmentioning
confidence: 58%
“…It is related to an individual, subjective approach to the patient and allows for the assessment of the impact of disease and treatment on functioning of the patient and their relatives in terms of physical, mental and social well-being. The purposefulness of measuring the quality of life in cancer patients was demonstrated by Montazieri, who stated that the global quality of life of patients before starting oncological treatment is an important predictor of survival [ 19 , 20 , 21 ]. Similarly, Li et al, based on a sample of over 400 cancer patients, presented results proving that health-related quality of life is a strong and independent predictor of overall survival [ 22 ].…”
Section: Discussionmentioning
confidence: 99%